Developing novel optogenetic tools in Caenorhabditis elegans - Baxter, Kieran Garry (The University of Edinburgh, 2023)
Proteins are biopolymers constructed from 20 canonical amino acids which, while limited in number, work together to carry out an extensive variety of functions essential to life. Genetic code expansion allows for the site-specific incorporation of non-canonical amino acids with novel functions not found in nature, creating proteins with unique properties that can be applied to tasks that are otherwise unachievable. Photocaged amino acids contain a bulky ’caging’ group conjugated to the side chain of a canonical amino acid. This caging group can render the protein inactive by blocking its active site, but can be rapidly removed by illumination with 365 nm light, restoring the canonical amino acid and allowing for the photoactivation of the protein. Photocaged amino acids have been previously used in Caenorhabditis elegans to develop tools for controlling gene expression, apoptosis, and protein-protein interactions. In this thesis, I give a general introduction on genetic code expansion and the use of photocaged amino acids, as well as the use of C. elegans as a model organism. I then explore the use of photocaged amino acids in developing optogenetic tools in C. elegans. The main focus of this thesis is the development of a photocaged FLP recombinase which can drive gene expression with high spatiotemporal control. I show that this can be done in two ways, by photocaging either the catalytic lysine residue, or the catalytic tyrosine residue. In both cases, expression of a target gene is inhibited by the use of an FRT-flanked transcriptional terminator, which can be excised by the photoactivated FLP to drive gene expression with single-cell resolution. This system provides a valuable tool for the study of functions of cells that could not be targeted by other methods. We demonstrate this by using photocaged FLP to drive expression of a channelrhodopsin in the PVC neurons, which do not have their own cell-specific promoter, allowing us to study the contributions of the PVCs in locomotion and sleep. I also discuss the use of photocaged amino acids in the generation of genetargeted random mutagenesis tools, an area of genetic screening that is so far underutilised in C. elegans. These tools are designed to be targeted to a specific gene of interest and generate a random set of mutations in the area, which would facilitate the study of that gene in reverse genetics experiments.
Keywords: optogenetic tools; Caenorhabditis elegans; biopolymers; Genetic code expansion; non-canonical amino acids; Photocaged; Photocaged amino acids; caging; photocaged FLP recombinase; spatiotemporal control; catalytic lysine residue; catalytic tyrosine residue; photoactivated FLP; PVC neurons; FRT-flanked transcriptional terminator